Analysis of the Effect of Service Quality on Customer Loyalty Through Customer Satisfaction on Cv. Tiga Bersaudara Sejahtera - Siti Mawardah Rojie; Fanlia Prima Jaya (Hut Publication Business and Management, 2022)
The purpose of this study was to determine the effect of Service Quality on Customer Loyalty through Customer Satisfaction at CV. Tiga Bersaudara Sejahtera either partially or simultaneously. This type of research uses a quantitative descriptive method. The population in this study are customers at CV. Tiga Bersaudara Sejahtera. The sample of this research was 24 respondents using a questionnaire. The data analysis technique used is multiple linear regression. The results of this study note that (1) partially Service Quality has a significant effect on Customer Satisfaction as proven by (2) partially Service Quality has a significant effect on Customer Loyalty (3) simultaneously Service Quality and Customer Satisfaction as intervening have a significant effect on Customer Loyalty. The researcher's suggestion for the company is that the company provides better service quality in order to always maintain customer satisfaction so that repeated purchases occur. The company can also continue to develop a food menu with even more variations in order to maintain service quality so as to maintain a sense of customer satisfaction with the catering food products provided.